2007
DOI: 10.1001/archsurg.142.6.554
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Interleukin 8 Gene Expression in Reflux Esophagitis and Barrett's Esophagus With Antireflux Surgery

Abstract: Hypothesis: Chronic inflammation of esophageal mucosa secondary to refluxed gastric juice increases gene expression of interleukin 8 (IL-8). Antireflux surgery can reduce this overexpression. Design: Prospective analysis of archival paraffinembedded tissue. Setting: Academic tertiary medical center. Patients and Methods: One hundred eight patients with reflux symptoms were classified according to pH monitoring and endoscopic and histologic findings. Twenty patients did not have reflux or mucosal injury; 47 had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 17 publications
(21 reference statements)
0
29
0
1
Order By: Relevance
“…In a Japanese study of patients with nonerosive reflux disease (NERD) with minimal mucosal involvement, as determined by endoscopy, IL-8 mRNA levels were increased compared with NERD patients with no mucosal involvement and with controls (63). After successful treatment with PPIs or Nissen fundoplication, IL-8 levels declined (55,83,138). High mucosal IL-8 levels predicted an increased relapse rate for GERD within 3 years, indicating a potential prognostic role for this cytokine (53).…”
Section: Inflammatory Mediators In the Inflamed Esophageal Mucosamentioning
confidence: 99%
See 1 more Smart Citation
“…In a Japanese study of patients with nonerosive reflux disease (NERD) with minimal mucosal involvement, as determined by endoscopy, IL-8 mRNA levels were increased compared with NERD patients with no mucosal involvement and with controls (63). After successful treatment with PPIs or Nissen fundoplication, IL-8 levels declined (55,83,138). High mucosal IL-8 levels predicted an increased relapse rate for GERD within 3 years, indicating a potential prognostic role for this cytokine (53).…”
Section: Inflammatory Mediators In the Inflamed Esophageal Mucosamentioning
confidence: 99%
“…IL-8 has been extensively studied in GERD and is expressed in high amounts in the affected mucosa of GERD patients (36,55,56,83,138). IL-8 is a powerful chemoattractant and activator of leukocytes and other nonimmune cells.…”
Section: Inflammatory Mediators In the Inflamed Esophageal Mucosamentioning
confidence: 99%
“…The latter can be seen as an adaptive response to gastro-esophageal reflux exposure. In contrast, other studies implicate a stepwise increase in the expression of IL-8 from esophageal reflux disease through Barrett's esophagus to esophageal adenocarcinoma [40,41]. The IL-8 receptors, CXCR1 and CXCR2, are constitutively expressed in esophageal mucosa, especially by epithelial cells and infiltrated leukocytes [42,43].…”
Section: Gastric Cancermentioning
confidence: 98%
“…Indeed, proton pump inhibitors (e.g. lansoprazole) and surgery reduce the levels of acids and consequently of IL-8, which results in reduced inflammatory response and tissue damage [36,41,[45][46][47]. Also the anti-inflammatory compound curcumin, which is a polyphenolic pigment isolated from the plant Curcuma longa, was found to inhibit esophageal activation and IL-8 release in response to acid [48].…”
Section: Gastric Cancermentioning
confidence: 99%
“…Amongst these, CXCL8 is reported as a molecular marker indicative of response to therapeutic procedures. For example, Oh et al [113] compared the expression level of CXCL8 between pre-and postoperation of Nissen fundoplication in reflux esophagitis. They found that CXCL8 expression was significantly reduced postoperatively, as measured by quantitative real-time polymerase chain reaction (qRT-PCR).…”
Section: Esophagusmentioning
confidence: 99%